Factors Influencing Participation in Physiotherapy Services Following a Total Shoulder Replacement Surgery: A Cross‐Sectional Survey - Rochelle Furtado; Marco Bandiera; Nevin Becker; Lisa Mitchell; Luca Paron; Tyler Shalansky; Dakota Turner‐Johnston; Joy C. MacDermid (Health Science Reports)
ABSTRACT Background When designing appropriate rehabilitation programs after a shoulder replacement, it is critical to consider the multitude of factors that can influence a patient's participation. Therefore, this study aims to quantitively understand the factors that affect access and participation to physiotherapy services after a shoulder replacement in older adults. Methods Our research team created an online of 58 questions, focusing on personal characteristics, geographic accessibility, socioeconomic status, preferences for care, social support, and cultural beliefs to understand potential barriers and facilitators to accessing services. Using a mixed‐methods approach, data was analyzed through quantitative descriptive statistics and interpretive descriptive methodology. Data was stratified by gender. Data collection took place in 2020–2022. Results A total of 51 (53% women) people participated in this survey; with the average age of 64.6 (9.4) years old. Gender heavily influenced patients' preferences on accessing care and physiotherapy services. Social factors, economic factors and personal factors emerged as potential barriers to participation in physiotherapy for women. Patient expectations differed by gender, as women prioritize return to daily activities (93%), whereas men prioritized sport/recreational activities (85%). Finally, preferences for delivery of physiotherapy differed based on gender, as men prefer in person (77%) and women prefer virtual. Conclusion This survey was able to investigate trends that influence participation to rehabilitation after a shoulder replacement, both quantitatively and qualitatively. This study is a starting point for future research to explore how factors such as gender roles and social expectations may affect individuals' participation in rehabilitation.